Different Strokes: A management dilemma - Gujjar, Arunodaya R. (Sultan Qaboos Univ Med J, 2018)
Stroke is a common medical emergency resulting from numerous pathophysiological mechanisms and with varied clinical manifestations; as such, the diagnosis of stroke requires diligent clinical assessment. When different stroke syndromes occur in the same patient, it may cause a dilemma in terms of diagnosis and management. This continuing medical education article describes an interesting patient with recurrent neurological events, highlighting the complex pathophysiological processes associated with cerebrovascular syndromes. It offers readers the opportunity to apply their own basic neuroscience knowledge and clinical skills to solve the challenges encountered during the course of diagnosing and treating this patient. Specifically, the article aims to familiarise readers with an approach to diagnosing brainstem strokes and the diverse manifestations of a common stroke syndrome.